2016
DOI: 10.1038/ng.3691
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of DUX4 and ERG in acute lymphoblastic leukemia

Abstract: Chromosomal rearrangements deregulating hematopoietic transcription factors are common in acute lymphoblastic leukemia (ALL).1,2 Here, we show that deregulation of the homeobox transcription factor gene DUX4 and the ETS transcription factor gene ERG are hallmarks of a subtype of B-progenitor ALL that comprises up to 7% of B-ALL. DUX4 rearrangement and overexpression was present in all cases, and was accompanied by transcriptional deregulation of ERG, expression of a novel ERG isoform, ERGalt, and frequent ERG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
295
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 262 publications
(324 citation statements)
references
References 56 publications
19
295
1
1
Order By: Relevance
“…Recurrent IGH ‐ DUX4 ( double homeobox 4 ) fusions, resulting in DUX4 overexpression and a unique gene expression signature, were very recently reported in up to 7% of childhood B‐ALL cases. DUX4 rearrangement results in loss of function of ERG ( ETS‐related gene ) via intragenic deletion or via induction of a dominant‐negative isoform that inhibits wild‐type ERG (Zhang et al , ). ERG‐DUX4 fusions have also been reported (Lilljebjorn et al , ).…”
Section: B‐cell Acute Lymphoblastic Leukaemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Recurrent IGH ‐ DUX4 ( double homeobox 4 ) fusions, resulting in DUX4 overexpression and a unique gene expression signature, were very recently reported in up to 7% of childhood B‐ALL cases. DUX4 rearrangement results in loss of function of ERG ( ETS‐related gene ) via intragenic deletion or via induction of a dominant‐negative isoform that inhibits wild‐type ERG (Zhang et al , ). ERG‐DUX4 fusions have also been reported (Lilljebjorn et al , ).…”
Section: B‐cell Acute Lymphoblastic Leukaemiamentioning
confidence: 99%
“…ERG‐DUX4 fusions have also been reported (Lilljebjorn et al , ). Despite frequent concomitant IKZF1 deletions, patients with DUX4 rearrangements appear to have excellent clinical prognoses with standard chemotherapy treatment (Clappier et al , ; Lilljebjorn et al , ; Yasuda et al , ; Zhang et al , ).…”
Section: B‐cell Acute Lymphoblastic Leukaemiamentioning
confidence: 99%
“…The majority of studies have shown that IKZF1 alterations are associated with poor outcome, both in ALL cohorts comprising multiple subtypes, and in BCR-ABL1 ALL, including cases treated with TKI (19, 2136). An exception is a subtype of ALL characterized by deregulation of the double homeobox gene DUX4 and the ETS family transcription factor ERG , in which IKZF1 alterations are common but not associated with poor outcome (37, 38). …”
Section: A Central Role For Ikzf1 Alterations In the Pathogenesis Ofmentioning
confidence: 99%
“…ERG-wt expression was not altered in relation to ERG status but 46% of ERG-related patients expressed a short ERG isoform, supposedly the ERGalt protein recently described in another ERG-related cohort [6] and shown to inhibit wild type ERG transcriptional activity.…”
Section: Discussionmentioning
confidence: 91%